The potential of non-native tree species to provide major ecosystem services in Austrian forests - Konic, Julia; Heiling, Carina; Haeler, Elena; Chakraborty, Debojyoti; Lapin, Katharina; Schueler, Silvio (Frontiers in Plant Science, 2024)
Forestry is facing an unprecedented challenging time. Due to climate change, major tree species, with until recently fulfilled major ecosystem services, are being lost and it is often unclear if forest conversion with other native or non-native tree species (NNT) are able maintain or restore the endangered ecosystem services. Using data from the Austrian Forest Inventory, we analysed the current and future (2081-2100, RCP 4.5 and 8.5) productivity of forests, as well as their protective function (avalanches and rockfall). Five different species change scenarios were considered for the replacement of a tree species failing in the future. We used seven native tree species (Picea abies, Abies alba, Pinus sylvestris, Larix decidua, Fagus sylvatica, Quercus robur and Quercus petraea) and nine NNT (Pseudotsuga menziesii, Abies grandis, Thuja plicata, Pinus radiata, Pinus contorta, Robinia pseudoacacia, Quercus rubra, Fraxinus pensylvanica and Juglans nigra). The results show that no adaptation would lead to a loss of productivity and decrease in tree species richness. The combined use of native and NNT is more favourable than purely using native species in terms of productivity and tree species richness. The impact of the different species change scenarios can vary greatly between the different environmental zones of Austria (Alpine south, Continental, and Pannonian zone). Especially, the Pannonian zone would benefit from the use of NNT in terms of timber production. For the protection against avalanches or rockfall in alpine regions, NNTs would not be an advantage, and it is more important if broadleaved or coniferous trees are used. Depending on whether timber production, protective function or tree species richness are considered, different tree species or species change scenarios can be recommended. Especially in the protective forest, other aspects are essential than in the commercial forest. Our results provide a basis for forest owners/managers in three European environmental zones to make decisions on a sustainable selection of tree species to plant in the face of climate change.